Improvement after Constraint-Induced Movement therapy is independent of infarct location in chronic stroke patients - Gauthier, Lynne V. (2009)
BACKGROUND AND PURPOSE: Disruption of the corticospinal tract at various locations in the brain has been shown to predict worse spontaneous motor recovery after stroke. However, the anatomical specificity of previous findings was limited by the categorical classification of infarct locations. Here we used computational methods to more precisely determine the specific anatomical locations associated with impaired motor ability. More important, however, our study also used these techniques to evaluate whether infarct location could influence motor outcomes following Constraint-Induced Movement therapy (CI therapy), a specific and controlled form of physical therapy. METHODS: Quantitative voxel-based analyses were employed to determine whether infarct location could predict either initial motor ability or clinical improvement following CI therapy in chronic stroke patients. RESULTS: Although corona radiata infarcts were associated with worse in-laboratory motor ability at pre-treatment, infarct location did not predict improvement in either the laboratory or the life situation after CI therapy. CONCLUSIONS: The extent of improvement from CI therapy does not depend on the location of neurological damage, despite there being a pre-treatment relationship between infarct location and in-laboratory motor ability. This dissociation could be explained by brain plasticity induced by CI therapy.